Meditasi Mindfulness Guna Meningkatkan Mindfulness Siswa SMA Sebagai Cara Menjaga Kesehatan Mental - Lesmana, Teguh (Devotion : Jurnal Pengabdian Psikologi, 2023)
Difficulties and challenges in the lives of teenagers who are in the transition period to adulthood, if they are not equipped with good adaptability, will cause problems with teenagers' mental health. One of the factors that influences teenagers' mental health is a feeling of gratitude. Regarding this gratitude factor, an approach that can be used to increase feelings of gratitude in teenagers is a mindfulness approach. Mindfulness is considered suitable for high school students because mindfulness is something that is applied in everyday life. In this research, what we want to prove is the role of mindfulness meditation in increasing high school students' mindfulness. The research subjects consisted of 92 Atisa Dipamkara High School students in grades 10 and 11. The method used was a quantitative research method that used SPSS for the data processing program. The design used is quasi-experimental research, a one-group pre-test post-test design. The measuring instrument used is the Mindfulness Attention Awareness Scale (MAAS), which has been adapted into Indonesian. The research results showed that there was a significant difference between before and after the mindfulness meditation training was given. Thus, the mindfulness meditation provided has been proven to significantly increase mindfulness in high school students.